PERAN KOMUNIKASI KEBUDAYAAN DALAM MERAJUT KERUKUNAN ANTAR UMAT BERAGAMA DI DESA KUTA GERAT KECAMATAN MUNTHE KARO - Muktarruddin Muktarruddin; Irma Oktavia; Dwiva Ramadhani Ginting; Ahmad Sakban Dwiva; Fadhlan Habib; Mansyursyah Margolang (Jurnal Ilmiah Wahana Pendidikan, 2023)
The culture that exists in each region often makes people, even those with different beliefs, unite and protect one another. It is inevitable that the Indonesian nation is a multicultural country. The motto Bhineka Tunggal Ika is a symbol that this country is a different country but will still be one. There are three elements in the religious system, namely the system of beliefs, the system of religious ceremonies, and the people who adhere to that religion, in every culture you will find these elements even in different forms. Inter-Religious Harmony Harmony is an accurate depiction of inter-religious harmony, the relationship is usually generally between adherents of one religion and another. The diversity that exists in Indonesia is very characteristic, starting from skin color, ethnicity, and language which will eventually unite and form peace. The research used in this research method is a qualitative method. This qualitative research will use a survey method in which this method will be used to obtain data directly and obtained through interviews.